The emotional path to influencing decision-making: harnessing emotions for better financial choices - Born, Nadja; Ashebir, Sophia; Brady, Samantha; D'Ambrosio, Lisa; Coughlin, Joseph (Frontiers in Behavioral Economics, 2024)
As life expectancy and expected years in retirement rise and family structures change, the need for personal financial protections, such as long term care (LTC) insurance, in managing financial risks associated with later life is expected to increase. Roughly half of American households are at risk of not being able to maintain their present standards of living post-retirement. Because both public and private health insurance programs typically do not cover LTC needs, which are associated with significant costs to a growing share of older adults, the potential demand for LTC further exacerbates the retirement savings crisis in the U.S. This high-powered study (N = 1450) with a U.S. national sample aimed to examine the impact of a framing intervention on participants' attitudes, emotions, and behavioral intentions toward LTC insurance. Our results suggest that the impacts of frames on attitude and behaviors around LTC were not direct, but instead acted through two different emotional pathways. First, we find that a loss framing intervention can effectively induce anxiety, which is associated with positive attitudes and intentions toward LTC insurance. Additionally, we find that a narrative framing of care choice can effectively induce a greater feeling of calmness, which is also associated with positive LTC insurance attitudes and intensions. Our study results suggest that both a loss/gain framing and a narrative framing, through different emotional pathways, have the potential to be helpful to nudge people to hedge against a financial risk associated with older age.